Anchovy dynamics and the colour of climate noise: Assessing climatic scenarios and exploitation strategies in the Gulf of Cádiz. (1st June 2018) - Ruiz, Javier; Rincón, Margarita M.
Abstract: This manuscript implements stochastic modeling to investigate the response of a European anchovy ( Engraulis encrasicolus ) stock to climatic forcing under different exploitation strategies. The model implements realistic parametrizations for defining the key environmental variables forcing recruitment in the Gulf of Cádiz. Despite the tight control the environment exerts on this population, model outputs and historical records indicate that stock signal is not the same as the forcing signal; instead, the time series of the stock signal is less red (more variance at higher frequencies) than the forcing variables. The response is also very sensitive to the exploitation strategy and to the colour (white versus red noise) assumed for the climatic forcing. These results indicate that establishing a safe management framework for this stock demands not only an assessment of an adequate exploitation strategy, but also an understanding of how this strategy interacts with the different colours of the climatic forcing.